Proteus mirabilis Targets Atherosclerosis Plaques in Human Coronary Arteries via DC-SIGN (CD209) - Xue, Ying; Li, Qiao; Park, Chae Gyu; Klena, John D.; Anisimov, Andrey P.; Sun, Ziyong; Wei, Xiang; Chen, Tie (Frontiers in Immunology, 2021)
Bacterial DNAs are detected in atherosclerotic plaques (APs), which suggest that a combination of chronic infection and inflammation may have roles in AP formation. A series of studies suggested that certain Gram-negative bacteria can interact with dendritic cell-specific intercellular adhesion molecule-3-grabbing non-integrin (DC-SIGN; cluster of differentiation (CD) 209) or langerin (CD207), thereby resulting in deposition of CD209s at infection sites. We wondered if Proteus mirabilis (a member of Proteobacteria) could interact with APs through CD209/CD207. First, we demonstrated that CD209/CD207 were also receptors for P. mirabilis that mediated adherence and phagocytosis by macrophages. P. mirabilis interacted with fresh and CD209s/CD207-expressing APs cut from human coronary arteries, rather than in healthy and smooth arteries. These interactions were inhibited by addition of a ligand-mimic oligosaccharide and the coverage of the ligand, as well as by anti-CD209 antibody. We concluded that the P. mirabilis interacts with APs in human coronary arteries via CD209s/CD207. It may be possible to slow down the progress of atherosclerosis by blocking the interactions between CD209s/CD207 and certain atherosclerosis-involved bacteria with ligand-mimic oligosaccharides.